The late outcomes of syngeneic hematopoietic stem cell transplantation in patients with blood disorders - A. A. Dmitrova; L. A. Kuz'mina; V. A. Vasil'eva; M. Yu. Drokov; E. N. Parovichnikova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Introduction. Syngeneic hematopoietic stem cell transplantation is a type of allogeneic stem cell transplantation when the donor of stem cells is a genetically identical (monozygotic) twin of the recipient. After this type of transplantation, there is no immunological conflict as the graft versus host disease, but at the same time, there is no positive effect of the graft-versus-leukemia effect. Aim: to assess the overall survival, event-free survival, probability of relapse, and transplant-related mortality rates associated with syngeneic stem cell transplantation. Patients and methods. In the National Research Center for Hematology from January 1988 to December 2018 we performed 654 allo-HSCT: 17 (2.5%) of them from a syngeneic donor. We performed a «paired analysis» with patients after allo-HSCT from a HLA-identical sibling donor. We included patients after allo-HSCT from an HLA-identical related donor (n = 28) in Group 1 and patients after syngeneic stem cell transplantation in group 2 (n = 14). Patients with aplastic anemia (n = 3) were excluded from the «paired analysis». Results. Patients after syngeneic stem cell transplantation did not develop a graft-versus-host disease. The relapse developed in 50% of cases (n = 7). Five patients (35.7%) died: 4 of them due to the relapse of the disease, and 1 - due to the graft failure. The relapse probability in patients after syngeneic HSCT was higher and amounted to 18.4% versus 54.2% (p = 0.047) for allo-HSCT from HLA-identical sibling donor and a syngeneic donor, respectively. Overall and event-free survival in patients after syngeneic HSCT is comparable to those in patients after allo-HSCT from an HLA-identical sibling donor. Conclusion. Syngeneic hematopoietic stem cell transplantation is justified in the absence of another related or unrelated donor of hematopoietic stem cells. The use of myeloablative conditioning regimens, peripheral blood stem cells as a source of stem cells, or high doses of nucleated cells/kg in the case of using bone marrow will improve post-transplant parameters in patients after syngeneic hematopoietic stem cell transplantation.